Improvement of Resistant Cow Breakers by Mean of Empowering Independent Energy Village Program of PT Pertamina Patra Niaga Fuel Terminal Parepare - Firman Firman; Antonius Primus (Journal of Wetlands Environmental Management, 2023)
Biogas has an important role as a substitute for energy derived from geothermal energy. Biogas has an important role in overcoming energy difficulties because the production and management process is not expensive, besides being friendly to the environment. Biogas is produced from processed animal waste, through a device known as a specially designed fixed dome-type biogas reactor. This study used a literature review through literature related to biogas production and management as well as field trials that took place in the Tangguh Village community, Watang Bacukiki Village, Parepare City, South Sulawesi. The research results prove that the use of biogas can save energy and reduce the impact of environmental damage.  These findings suggest that the use of biogas can be practiced further as the CSR program of PT Pertamina Patra Niaga Fuel Terminal Parepare.